Developing Interactive Multimedia-based E-Learning to Teach Reading - Sri Wiyanah; Sofia Farida Rahman (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2024)
Teaching phenomenon during Covid-19 Pandemic demanded teacher used platforms for online learning. Teaching via online learning caused students' learning motivation decreases. Students were passive during learning. Based on school regulations, teachers can only use two platforms for online learning, namely, Google Class Room and WhatsApp. Teachers were not allowed to upload files that were too large so that it would burden the students, and the types of files that can be sent on the two platforms were also very limited. The aims of the study are to identify students’ need for learning and develop appropriate interactive multimedia-based e-learning to teach reading. This was Research and Development study which employed ADDIE Design. The study was conducted for the tenth-grade students of SMAN 3 Bantul. The result showed the target needs most of the students choose to master English and can read English text with good pronunciation are their goals. The learning needs as determined by the needs analysis are divided into input, planning, methods, the role of the teacher, and environment. In addition, Interactive learning multimedia developed using ADDIE in the form of Microsoft PowerPoint. The menus consisted of Home Page, Main Menu, and Extras Menu. The mean score for the content aspect was 3.86 and the media aspect was 3.625 which both were categorized as “very good”. The mean of the implementation and interview to the students’ response is 87.75/100 points. In conclusion, interactive multimedia is appropriate and feasible in teaching and learning reading.